EFEKTIVITAS PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SMP NEGERI 1 WONOSARI - Saputri, Widiya Ayu; Nurrohmah Widi Nastiti; Ismu Ardiyanto (STISIP Widyapuri Mandiri Sukabumi, 2025)
The aim of this research is to find out the effectiveness of the project to strengthen the profile of Pancasila students at SMP N 1 Wonosari and what factors support the effectiveness of the project to strengthen the profile of Pancasila students at SMP N 1 Wonosari. This research was carried out at SMP Negeri 1 Wonosari, whose address is Purbosari, Wonosari, Kec. Wonosari, Gunungkidul Regency. The research method used in this research is descriptive qualitative, the data used consists of two sources, namely primary data and secondary data. Determining informants was carried out using the purposive sampling method. The data collection techniques that researchers use are observation, interviews, and documentation. The results of this research are that the implementation of P5 at SMP N 1 Wonosari has been running effectively. Several indicators such as understanding the program, accuracy of targets, timeliness, achievement of goals, and real changes in students showed positive results. However, there were obstacles related to the implementation of socialization at the beginning of the school year which was not followed by all teachers which resulted in the need for further coordination between teachers so that implementation P5 can be well coordinated. P5 succeeded in strengthening student character according to the Pancasila profile, such as increasing student independence, cooperation, and creativity. Strong leadership factors, well-managed resources, and active involvement of stakeholders also support the smooth running of the program so that the entire P5 program at SMP N 1 Wonosari has a positive impact on the formation of student character.